HUBUNGAN TINGKAT KECEMASAN DENGAN SIKLUS MENSTRUASI PADA MAHASISWI TINGKAT AKHIR - Veronica Silalahi (JURNAL KESEHATAN MERCUSUAR, 2021)
Menstruation is a natural process in every woman and repeats itself every month. Irregular menstrual cycles are one of the signs of menstrual disorders and can be caused by anxiety. The phenomenon found by female students has anxiety with the final task and the menstrual cycle is not normal. The study's aim to analyze the relationship anxiety levels and the late-level menstrual cycle of St.Vincentius a Paulo College of Health Sciences, Surabaya. Design with correlation studies with a cross-sectional. The sample number was 56 respondents using the Simple Random Sampling technique. Anxiety levels were measured by the Psychometric Properties of The Depression Anxiety Stress Scale 42 (DASS 42) questionnaire and the menstrual cycle with menstrual cycle questionnaire. The results showed 38% had very severe anxiety, 23.2% no anxiety, 19.6% severe anxiety, 12.5% moderate anxiety, 7.1% mild anxiety, and more than half (61%) had normal menstrual cycles. Analysis of data with spearman rank test with a value of p = 0.098 (p>0.05) which means there is no relationship between anxiety levels and menstrual cycles in final-level students. Irregular menstrual can be caused by other factors such as weight, physical activity. College students can maintain a diet, regular exercise, and manage self-anxiety. Keywords : menstrual cycle, anxiety level